Confinement and restrictive measures against young people in the Nordic countries – a comparative analysis of Denmark, Finland, Norway, and Sweden. Issue 2 (3rd July 2022) - Enell, Sofia; Andersson Vogel, Maria; Henriksen, Ann-Karina Eske; Pösö, Tarja; Honkatukia, Päivi; Mellin-Olsen, Bård; Hydle, Ida Marie
ABSTRACT: This article reviews and compares the use of confinement and other restrictive measures against young people under 18 in child welfare and/or the criminal justice systems in Denmark, Sweden, Finland, and Norway. Young people are confined for a variety of reasons, including protection, care, treatment, and punishment. However, confinement of young people is a contested issue because it can be viewed as necessary but also potentially harmful. Comparison of legislation and practices reveals that while there are some similarities in the service provisions for young people, there are also significant disparities among the four countries regarding the organization, function, and frequency of the use of confinement and restrictive measures. While Denmark and Sweden use secure welfare institutions, Finland and Norway apply other restrictive measures. Despite the differences in approaches to confinement in the Nordic countries, the use of confinement is guided by the principle of the child's best interest, and the child welfare system is the main frame for confinement and intervention. The article discusses these disparate practices from the perspective of children's rights and identifies new avenues for research and practice.